Morphological Phase Diagram of Biocatalytically Active Ceria Nanostructures as a Function of Processing Variables and Their Properties. Issue 12 (2nd October 2013) - Sakthivel, Tamilselvan; Das, Soumen; Kumar, Amit; Reid, David L.; Gupta, Ankur; Sayle, Dean C.; Seal, Sudipta
Abstract We rationalize how fluorite‐structured CeO2, which is crystallographically isotropic, can grow anisotropically (without templates) to form nanoparticles, rods, and cubes. In particular, single‐crystalline and monodispersed cubic CeO2 nanoparticles, nanorods, and nanocubes have been selectively synthesized by a very simple, efficient, and economical hydrothermal process using different NaOH concentrations, and Ce(NO3)3 as the cerium precursor. High‐resolution transmission electron microscopy reveals nanomaterials with differently exposed crystal planes: {111} and {100} for nanoparticles, {110} and {100} for nanorods, and {100} for nanocubes. During the preparation of the CeO2 nanomaterials, the formation of intermediate anisotropic Ce(OH)3 species under basic conditions and their conversion into CeO2 at higher temperature are key factors responsible for the shape evolution. Atomistic computer simulations were used to help rationalize how the synthetic conditions impact upon the morphology of the nanomaterial. The synthesized CeO2 nanoparticles and nanorods demonstrate higher catalase mimetic activities than the nanocubes.